INOVASI SUMBER BELAJAR BERBASIS PROYEK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA PENGAJARAN TITRASI ASAM BASA - Hilda Pratiwi; Ajat Sudraja; Ramlan Silaban (PROSIDING SEMINAR KIMIA, 2022)
Students' motivation in learning activities carried out in the laboratory really needs to be improved in order to improve Higher Order Thinking Skills in Teaching Acid-Base Titrations. This study aims to see the innovation of project-based learning resources in improving student learning outcomes in acid-base titration learning. This research is a development research with the ADDIE development model (Analysis, Design, Development, Implement, Evaluation. The subjects of this study were students of class PSPK D 2019 with purposive sampling technique. Research data were collected through innovative observation sheets of project implementation. The questionnaire refers to the eligibility criteria BSNP, and interviews.To find out the laboratory-assisted project- based learning innovation on students' learning motivation was analyzed using an independent sample t-test with the help of SPSS 25. Keyword: Innovative, Higher Order Thinking ability, and Project-Based Learning.